Defiance - Hobbs, Valerie (New York : Farrar Straus Giroux, 2005)
While vacationing in the country, eleven-year-old Toby, a cancer patient, learns some important lessons about living and dying from an elderly poet and her cow.
"Frances Foster books."
5.8
5-8
Keywords: Death -- Juvenile fiction; Hope -- Juvenile fiction; Cancer -- Juvenile fiction; Poets -- Juvenile fiction; Cows -- Juvenile fiction; Country life -- Juvenile fiction; Death -- Fiction; Hope -- Fiction; Cancer -- Fiction; Poets -- Fiction; Cows -- Fiction; Country life -- Fiction; Death -- Fiction; Hope -- Fiction; Cancer -- Fiction; Poets -- Fiction; Cattle -- Fiction; Country life -- Fiction